Peran Media Digital dalam Bingkai Etnopedagogik sebagai Upaya Optimalisasi Pencapaian Kualitas Pendidikan Anak Usia Dini Masa Depan - Gilar Gandana; Nuraly Masum Aprily; Aini Loita; Rifki Ahmad Fauzi; Chusna Arifah; Risa Arosyidah (Jurnal Elementaria Edukasia, 2023)
The digitalization program for early childhood education media in the era of the industrial revolution 4.0 is an opportunity as well as a challenge for educational inventors in the world. This opportunity can be used as an exploratory land for the development of science for educational media inventors. On the other hand, the challenges are related to the clash of value systems and consistency in strengthening the integration of the conservation function system with the educational innovation function. In this context, challenge does not mean weakness, but for scholars it is a form of motivational strength for the practical development of knowledge to be used as material for increasing self-capacity as a true scientist. Thus, the opportunities and challenges that arise in this study become a source of energy to overcome anxiety about the future of education. With regard to ethno-pedagogy which is the contextual realization of human imagination in terms of human values ​​and norms, it has a very important role in presenting every digital product that is created. So that the process of integrating conservation values ​​with educational innovation values ​​can show logical consequences for achieving the expected quality of early childhood education in the future.